1975
DOI: 10.1104/pp.56.4.550
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of α-Farnesene in the Development of Chilling Injury in Bananas

Abstract: The levels of the sesquiterpene hydrocarbon, a-farnesene were found tobe higher in green bananas (Musa accuminata AAA) that were more susceptible to the development of chilling injury. The levels of a-farnesene were further increased by storage of the fruit at low temperature.chilling. The fruit from each district was held at 0 C and 20 C in air. At various intervals, a sample of peel (40 g) was obtained from two fruit in each treatment. The volatile compounds were obtained from the tissue by vacuum sublimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This is mainly due to the long held assertion that apples are relatively non chillingsensitive, and that the injury symptoms only occur after prolonged storage at very low temperatures. The likelihood of a-farnesene being involved in the development of CI in other fruits was first noted by Wills et al(1975) who found that bananas accumulated high levels of afarnesene when subjected to chilling. This study shows that a-farnesene was present in citrus fruit, and that it was closely involved in the development of CI in the fruit when chill stressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to the long held assertion that apples are relatively non chillingsensitive, and that the injury symptoms only occur after prolonged storage at very low temperatures. The likelihood of a-farnesene being involved in the development of CI in other fruits was first noted by Wills et al(1975) who found that bananas accumulated high levels of afarnesene when subjected to chilling. This study shows that a-farnesene was present in citrus fruit, and that it was closely involved in the development of CI in the fruit when chill stressed.…”
Section: Discussionmentioning
confidence: 99%
“…has been shown by Nordby and McDonald (1990) to Recently, a number of studies have implicated possess protective properties against CI development in putrescine, squalene and a-farnesene of being involved grapefruit. Wills et al (1975) implicated the unsaturated in the low temperature injury of plant products.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the α-farnesene content of 'Delicious' apples stored at 0 °C and 5 °C revealed that α-farnesene biosynthesis is 1.5-to 3-fold higher at 0 °C than at 5 °C at 8 and 10 weeks after harvest (data not presented). Wills et al (1975) found that αfarnesene levels of 'Dwarf Cavendish' bananas (Musa acuminata Colla) can be induced by low temperature storage. As well, in 'Anjou' pears (Pyrus communis L.) that contain similar levels of α-farnesene as in apples, α-farnesene levels can be increased 6fold by holding fruit for 3 d at 0 °C compared with those stored at 10 °C (Rupasinghe, Paliyath and Murr, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of farnesene production has been shown to significantly decrease oxidative cell injury. 21,22 This effect, however has not been previously demonstrated in mammalian studies…”
Section: Discussionmentioning
confidence: 80%
“…20 Farnesene, a close derivative of Z,Z-farnesol, has been found to play a significant role during oxidative injury of eukaryotic cells. 21,22,23 When the autoxidation of this compound occurs in-vivo, cell injury and death have been observed. The inhibition of farnesene production has been shown to significantly decrease oxidative cell injury.…”
Section: Discussionmentioning
confidence: 99%